From field to museum tray: shrinking of the Mallard Anas platyrhynchos - Williams, Murray (Wildfowl, 2017)
Four commonly-recorded body measurements were collected from fresh specimens of Mallard Anas platyrhynchos and of captive-raised Mallard Ã— Grey Duck A. superciliosa hybrids, and the same specimens were measured again 25+ years later to determine the extent of tissue shrinkage. There was little shrinkage in bill length but average shrinkage in bill widths, tarsus lengths and wing lengths were between 3.0â€“4.7%, with changes in bill width and tarsus length being the most variable and extreme. Correction values to allow the combining of field and museum specimen measurements are provided.